Brassware cottage industry in Kuala Terengganu permanent mould design and diversification / Osman Ab.Rahman and Mohd.Faudzir Abu Bakar - Ab.Rahman, Osman; Abu Bakar, Mohd. Faudzir (1985)
This project is the proceeding of the former final year project in December 1982. “ study on the brassware cottage industry in Kuala Trengganu, problem identification and improvement of the process and the quality" by En.Azman Muda and En. Ab.Rahman Mat Yusoff. The purpose of this project is to find out the possibilities of solving the problem arised in the existing process. There are few possibilities suggested by the writer in the previous report and one of them is by permanent mould casting. What is permanent mould? It is a metal mould, consisting of two or more parts which is used in repeating processes for a batch of production. In this project, the writer will briefly describe the existing process and the problem faced in the industry. And the main content of the project is on the permanent mould design.